Novel imaging techniques for diabetic macular edema - Lobo, CL (1999)
Retinal edema should be defined as any increase of water of the retinal tissue resulting in an increase in its volume. It may be of cytotoxic or vasogenic origin. Development of vasogenic macular edema is dependent on a series of factors such as blood pressure, blood-retinal barrier permeability, retinal cell damage, retinal tissue osmotic pressure and retinal tissue compliance. Objective measurements of retinal thickness are now possible using the Retinal Thickness Analyser. Localised measurements of blood-retinal barrier permeability may also be obtained using the Retinal Leakage Analyser, a modified confocal scanning laser fluorometer, while obtaining simultaneously angiographic images of the choroid and retina. These new imaging techniques show that cytotoxic and vasogenic retinal edema may occur independently in the early stages of diabetic retinopathy. These findings offer new perspectives for designing novel therapeutic strategies.